Shale's Pore Structure and Sorption-Diffusion Characteristics: Effect of Analyzing Methods and Particle Size - Sharifigaliuk, H. (American Chemical Society, 2022)
The delineation of pore size and surface area distribution and methane sorption-diffusion capacity in gas shale reservoirs is crucial for the estimation of storage capacity, anticipating flow characteristics, and field development. A systematic approach and guidelines are needed for the analysis of the pore size and surface area distribution of shale formations. The effect of shale sample size on the gas sorption and diffusion properties is not well understood either. The low-pressure nitrogen adsorption technique is a prevalent method for pore characterization of nanoporous shale formations. Although researchers adopted some corrections to the classical method for the analysis of pore size and surface area distribution, there is a significant mismatch between different approaches in depicting fine mesopore size and surface area (2-10 nm). In this study, the classical methods and density functional theory are employed to comparatively analyze the pore characteristics of some shale and clay samples for their applicability, efficacy, and consistency issues. Furthermore, the effect of shale particle size on the methane sorption capacity and diffusion is being investigated. It seems that confinement stress has less of a considerable effect on methane sorption (6 decrease). However, crushing shale rocks into smaller particles can significantly overestimate the methane adsorption capacity. The methane diffusion coefficient also increases with increasing the shale particle size by more than an order of magnitude. Â©